2017
DOI: 10.1038/srep41909
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dietary analysis of two sympatric felids in the Mountains of Southwest China biodiversity hotspot and conservation implications

Abstract: Dietary information is lacking in most of small to mid-sized carnivores due to their elusive predatory behaviour and versatile feeding habits. The leopard cat (LPC; Prionailurus bengalensis) and the Asiatic golden cat (AGC; Catopuma temminckii) are two important yet increasingly endangered carnivore species in the temperate mountain forest ecosystem in Southwest China, a global biodiversity hotspot and a significant reservoir of China’s endemic species. We investigated the vertebrate prey of the two sympatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 47 publications
0
66
1
Order By: Relevance
“…Many metabarcoding diet studies make use of both %FOO and POO (e.g., Xiong et al, 2017). POO provides a convenient view as each food taxon contributes a percentage of total diet (unlike %FOO which does not sum to 100%).…”
Section: Focalmentioning
confidence: 99%
“…Many metabarcoding diet studies make use of both %FOO and POO (e.g., Xiong et al, 2017). POO provides a convenient view as each food taxon contributes a percentage of total diet (unlike %FOO which does not sum to 100%).…”
Section: Focalmentioning
confidence: 99%
“…Many metabarcoding diet studies make use of both %FOO and POO (e.g. Xiong et al 2017). POO 187 provides a convenient view since each food taxon contributes a percentage of total diet (unlike 188 %FOO which does not sum to 100%).…”
mentioning
confidence: 99%
“…Other studies have reported far lower success rates from faeces e.g. 47% to 71% in Atlantic puffin (Fratercula arctica) (Bowser et al 2013); 73% in Panthera species (Xiong et al 2017).…”
Section: Buccal Swabs and Dietary Analysesmentioning
confidence: 87%